The Association Between Service Quality and Patient Satisfaction Among Obstetric and Gynecologic Emergency Patients - Naura Annisa Ghasani; Sulistiawati Sulistiawati; Budi Prasetyo; Widati Fatmaningrum (Universitas Muhammadiyah Palembang, 2026)
Background: Public demands for quality healthcare services are the focus of reference for continuous improvement in healthcare management. The quality of emergency obstetric care contributes to the maternal mortality rate (MMR) in Indonesia. Objective: To analyse the relationship between Service Quality (RATER) and the level of satisfaction of obstetric and gynaecology emergency patients in the emergency room of Fatimah Hospital, Lamongan. Methods: This study used an observational and explanatory cross-sectional design. The population was all obstetric and gynaecological patients who visited the emergency room of Fatimah Hospital, Lamongan, from December 2025 to February 2026, totalling 484 patients using incidental sampling. Independent variables: Reliability, Assurance, Tangibles, Empathy, and Responsiveness. Dependent variable: Patient Satisfaction. The instrument used to measure service quality is the SERVQUAL questionnaire, while patient satisfaction is measured according to IKM Decree No. 25/M.PAN/2/2004. Data were analyzed using the Spearman correlation test with a significance level of 0.05. Results: The results showed a relationship between Reliability (r=0.161, p<0.001), Assurance (r=0.290, p<0.001), Tangibles (r=0.194, p<0.001), Empathy (r=0.328, p<0.001), and Responsiveness (r=0.212, p<0.001) with patient satisfaction. Conclusion: Service quality based on SERVQUAL dimensions is significantly associated with patient satisfaction in emergency obstetrics and gynaecology services at the emergency room of Fatimah Hospital, Lamongan.